Anxiety and Depression in Patients With Pulmonary Arterial Hypertension in Northwest China: A Cross-Sectional Study - Zhang, Juxia; Yin, Yuhuan; Wen, Yujie; Shi, Fugui; Wang, Jiancheng (Frontiers in Psychiatry, 2022)
Objective: Pulmonary arterial hypertension (PAH) is a rare life-threatening and incurable disease. Although symptoms of depression and anxiety have been widely reported, these traits and associated factors have not been systematically assessed in Northwest China. Methods: A cross-sectional study was conducted between March 2020 and February 2021. 106 PAH patients in Northwest China were evaluated by Self-rating Anxiety Scale (SAS) as well as the Self Rating Depression Scale (SDS) questionnaire. Results: Overall, the included patients had particularly high depressive symptoms (70.09%), while anxiety among them were 17.55%. Multivariate linear regression revealed that patients with lower age (P=0.04), female (P<0.01), smoking(P<0.01), WHO functional class Ⅲ/Ⅳ (P<0.01), higher mean pulmonary hypertension (P<0.01), lower left ventricular ejection fraction(P<0.01), and lower six-minute walk distance (P<0.01) had higher anxiety scores. (Table 4) Patients who lived in rural areas (P=0.01), smoking (P<0.01), WHO functional class Ⅲ/Ⅳ (P<0.01), higher mean pulmonary hypertension (P=0.04), lower six-minute walk distance (P<0.01), and college degree or above had higher depression scores (P=0.02) (Table 5). Conclusions: Mental health problem such as depressive are common among patients with PAH in Northwest China. Patients characteristics such as smoking status, WHO functional class, and six-minute walk distance were related to anxiety and depression scores. Thus, early detection of mental health such as depressive and anxiety among should be detected in PAH patients. Meanwhile, interventions against these problems should be used to improve such patients’ mental status.